Інтегральні рівняння зі змінною верхньою межею динамічної задачі теорії пружності в напруженнях у неоднорідному довгому порожнистому ортотропному циліндрі - Калиняк, Б.М. (Доповіді НАН України, 2010)
Запропоновані інтегральні рівняння та інтегральні умови для розв'язування динамічної задачі теорії пружності і незв'язаної термопружності у неоднорідному довгому ортотропоному порожнистому циліндрі, отримані безпосереднім інтегруванням відповідних рівнянь руху та суцільності у напруженнях. Такий підхід дозволяє одержувати наближені аналітичні розв'язки задач пружності і термопружності без застосування інтегральних перетворень або розкладу в ряди за власними функціями. The integral equations with variable upper limits and a separable kernel, as well as integral conditions for solving the dynamical problem of elasticity and uncoupled thermoelasticity in an inhomogeneous long hollow orthotropic cylinder, have been proposed. The equations have been obtained by the procedure of a direct integration of the corresponding differential equations of motion and the compatibility equations in terms of stresses. This approach makes it possible to determine an approximate analytical solution of problems of elasticity and thermo-elasticity without determining the potential functions and without the methods of integral transformations and the expansion in series in eigenfunctions.